Has expansion of mobile phone and internet use spurred financial inclusion in the SAARC countries? - Sanjaya Kumar Lenka; Rajesh Barik (Financial Innovation, 2018)
Exclusion from the mainstream financial world is a burden on the poor of many countries. The proliferation of new mobile and online financial services, such as e-banking, money transfers, and payment processing has the potential to provide access to basic financial products and services to financially excluded people. The purpose of this study was to investigate the effects of the growth of mobile phone and Internet use on financial inclusion in the South Asian Association for Regional Cooperation (SAARC) countries from 2004 to 2014. We applied principal component analysis to construct a financial inclusion index that served as a proxy variable for the accessibility of financial services in the SAARC countries. Using three different models-the fixed effect, random effect, and panel correction standard errors modelsthis study discovered a positive and significant relationship between the growth of financial inclusion and expansion of both mobile phone and Internet services. Moreover, an empirical study of the control variables showed that the levels of income and education were positively associated with financial inclusion, whereas the size of the rural population and unemployment were negatively related to financial inclusion. In addition, the empirical estimates posit a unidirectional causal flow from the growth of mobile and Internet services to expanded financial inclusion in the SAARC countries.
Keywords: B26; F36; F38; G2F; 650; Financial inclusion; Fixed effect; Random effect; Panel corrected standard errors; SAARC